Increasing Student Activity and Learning Outcomes Using the BERANI Model in Elementary School - Eklima, Mawahesa; Sari, Raihanah (Institut Agama ISlam Negeri Palangka Raya, 2024)
The problem in this research is the low activity and learning outcomes of students in PPKn content. This research aims to determine the activities of educators, as well as increasing the activities and learning outcomes of students. This research uses a qualitative approach with the type of Classroom Action Research (PTK) which was carried out in 4 meetings in class IV of SDN Mawar 2 Banjarmasin in the even semester of the 2023/2024 academic year. The research instrument uses observation sheets and evaluation tests for student learning outcomes. Data analysis in this research uses descriptive analysis techniques and is explained using tables, graphs and interpretation with percentages. Based on the findings of this research, educator activity increased at each meeting until it reached a score of 28 at meeting 4 which met the